Case study: people with severe mental disorders with physical mobility barriers after in pasung - Veni Eka Septiyana Hidayanti; Mizam Ari Kurniyanti; Soebagijono; Alfianto, Guntur (Journal of health research and technology, 2023)
Introduction: The number of cases of shackling in people with mental disorders (ODGJ) in Indonesia has caused several factors for ODGJ, one of which is being able to experience barriers to physical mobility, this is because shackling has been carried out for several years causing muscle weakness and limited participants' range of motion. Based on these problems, it is necessary to do Range of Motion (ROM) exercises to help increase muscle strength and train clients to be able to walk as before. Purpose: To explore the management of nursing care for people with severe mental disorders who experience barriers to physical mobility after being shackled. Methods: This research method uses a quantitative and qualitative descriptive approach with a case study design using a nursing care model with a total of 2 participants, data collection was carried out from September to October 2022, the tools used were a sphygmomanometer, stethoscope, thermometer, penlight, and guide documentation assessment. Results : Participants were able to carry out nursing actions in generalist nurse therapy for Physical Mobility Barriers. In the final stage it was found that the two participants had different results where participant 1 entered at level 3 while participant 2 entered at level 2. This was due to the support and motivation of the family who always accompanied the participants when doing range of motion exercises. Conclusions: The main problem that arose in both participants was physical mobility barriers due to post pasung, with the final result being the level of independence in participants, namely participant 1 entered at level 3 and participant 2 entered at level 2.